Teknik Terobosan untuk Membantu Siswa dalam Mempelajari Grammar - Puspitasari, Indah (Jurnal Penelitian Pendidikan, 2023)
This research aims to determine the students' responses to the groundbreaking grammar teaching techniques after their boredom with conventional teaching methods. The digital learning platform of the British Council Learn English website combined with communicative games used by the researcher. This research is descriptive qualitative. Using purposive sampling, twenty-five students from the second semester in the English Study Program of STKIP PGRI Pacitan became the selected sample. The result of this study showed that 74% of students need breakthrough techniques to assist them in learning Grammar, 68% of students agree that the methods used by researchers make students understand grammar lessons, 80% of students argued that implementing the British Council Learn English website combined with communicative language game is quite effective in improving students' understanding of Grammar.